Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/papr.12644
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Leads After Permanent Implant in Spinal Cord Stimulator Systems

Abstract: To our knowledge this is the first descriptive analysis of the frequency of single- and dual-lead SCS systems. This report indicates that dual-lead systems are most often placed and both leads are required for optimal patient therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Mekhail et al reported a higher incidence of FBSS (33.2%) diagnosis in retrospective review of 707 SCS patients . Likewise, Sanders et al in a review of 259 SCS patients reported FBSS (40.5%) and CRPS (21.2%) as the most common indications for SCS, amongst other non‐spine‐related indications such as angina (12.4%), and peripheral neuropathy‐related pain . FBSS and CRPS widely remain the most common indications for SCS till date .…”
Section: Discussionmentioning
confidence: 99%
“…Mekhail et al reported a higher incidence of FBSS (33.2%) diagnosis in retrospective review of 707 SCS patients . Likewise, Sanders et al in a review of 259 SCS patients reported FBSS (40.5%) and CRPS (21.2%) as the most common indications for SCS, amongst other non‐spine‐related indications such as angina (12.4%), and peripheral neuropathy‐related pain . FBSS and CRPS widely remain the most common indications for SCS till date .…”
Section: Discussionmentioning
confidence: 99%
“…From the time of Shealy, leads and where they are placed have evolved from the vitallium and platinum single electrodes placed surgically at the corresponding pain location to a wide selection of percutaneous leads and multicolumn paddles placed largely in the T8-T10 levels for back and leg pain relief. 1,52,53 Multicolumn leads allowed for better energy shaping, which could create longitudinal tripoles and activate transverse electric fields. 52,54 Our current armamentarium of paddle leads contains 8 to 32 contacts.…”
Section: Paddle Leadsmentioning
confidence: 99%
“…1,52,53 Multicolumn leads allowed for better energy shaping, which could create longitudinal tripoles and activate transverse electric fields. 52,54 Our current armamentarium of paddle leads contains 8 to 32 contacts. 53 Paddle lead placement requires full laminectomy and/or hemilaminectomy approaches.…”
Section: Paddle Leadsmentioning
confidence: 99%
“…From a pragmatic standpoint, most interventional pain physicians use dual leads with the assumption that they allow for more versatile programming and better pain coverage (15,17,27,51,58). It has also been conjectured that dual leads serve as a safeguard against lead migration by expanding one's options for salvage reprogramming in the event that lead migration does occur (17,27,59). Incidentally, reports of the superiority of single vs dual leads have been mixed (15,51,(58)(59).…”
Section: E27mentioning
confidence: 99%
“…It has also been conjectured that dual leads serve as a safeguard against lead migration by expanding one's options for salvage reprogramming in the event that lead migration does occur (17,27,59). Incidentally, reports of the superiority of single vs dual leads have been mixed (15,51,(58)(59). Although this retrospective analysis shows no differences between single vs dual leads in our study cohort, we anticipate that larger well-designed controlled trials may help ascertain which practice is more cost-effective (60).…”
Section: E27mentioning
confidence: 99%